Review on Evolution of Patient Care Models (International Journal of Progressive Research and Innovation in Science, Engineering, Technology, Commerce, Management and Law (IJPRISETCML), 2025)
This transformation requires a commitment to ongoing training, stakeholder engagement, and the implementation of effective communication strategies that prioritize the patient experience.By fostering a culture of patient-centered care, healthcare organizations can significantly enhance patient satisfaction and outcomes, ultimately leading to a more effective healthcare system (- et al., n.d.).This commitment not only improves individual patient experiences but also fosters trust and collaboration among healthcare providers, creating a more resilient healthcare environment.
Keywords: Patient-Centered Care; Patient Satisfaction; Healthcare Communication; Healthcare System Resilience; Healthcare; Interoperability; Remote Patient Monitoring